Superior lubrication properties of biomimetic surfaces with hierarchical structure. (March 2018) - Lu, Yan
Abstract: In this study, a new method to fabricate biomimetic engineering surfaces with lotus leaf-like hierarchical microstructures is explored. Contact angle tests were performed to study the influences of the structures on the surface hydrophobic properties. Air lubrication resulted in hydrophobicity and consequently reduced the liquid-solid contact. The superior lubrication behaviour of a biomimetic hierarchical surface was observed by tribology experiments. Simulation results indicated that by improving hydrophobicity, the frictional drag was reduced by a significant amount because of the large fraction of air. It was found that introducing the superposition of microscale hemispherical papillae and branch-like nanostructures has a dramatic positive effect in reducing frictional drag results because 99% of liquid-solid interface was replaced by air-liquid interface. Highlights: The fabrication method was proposed to realize the hierarchical structure design in the practice. Microstructure may help surface switch between hydrophilicity, hydrophobicity and superhydrophobicity. Wettability test results were used to explain the friction drag of the surface could be reduced by using air lubrication. Friction coefficients affected by multi-scale structure surface were studied by both experimental and simulation method. The most desired hierarchical structure with superior lubrication property is presented.